Comparing acquisitions and divestitures - Mulherin, J.Harold; Boone, Audra L (Journal of Corporate Finance, 2000)
We study the acquisition and divestiture activity of a sample of 1305 firms from 59 industries during the 1990–1999 period. Consistent with the importance of restructuring activity during the 1990s, we find that half of the sample firms are acquired or engage in a major divestiture. Consistent with the notion that economic change is a source of the observed restructuring activity, we find significant industry clustering in both acquisitions and divestitures. We also study the announcement effects of the two forms of restructuring and find that both acquisitions and divestitures in the 1990s increase shareholder wealth. Moreover, the wealth effects for both acquisitions and divestitures are directly related to the relative size of the event. The symmetric, positive wealth effects for acquisitions and divestitures are consistent with a synergistic explanation for both forms of restructuring and are inconsistent with nonsynergistic models based on entrenchment, empire building and hubris.